Interrelationships among soil water regime, irrigation and water stress in the grapevine (Vitis vinifera L.) - Van Zyl, Jan Louis (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1984.